The ryanodine receptor–calstabin interaction stabilizer S107 protects hippocampal neurons from GABAergic synaptic alterations induced by Abeta42 oligomers. (15th November 2022) - Hidisoglu, Enis; Chiantia, Giuseppe; Franchino, Claudio; Tomagra, Giulia; Giustetto, Maurizio; Carbone, Emilio; Carabelli, Valentina; Marcantoni, Andrea
Abstract : Abstract: The oligomeric form of the peptide amyloid beta 42 (Abeta42) contributes to the development of synaptic abnormalities and cognitive impairments associated with Alzheimer's disease (AD). To date, there is a gap in knowledge regarding how Abeta42 alters the elementary parameters of GABAergic synaptic function. Here we found that Abeta42 increased the frequency and amplitude of miniature GABAergic currents as well as the amplitude of evoked inhibitory postsynaptic currents. When we focused on paired pulse depression (PPD) to establish whether GABA release probability was affected by Abeta42, we did not observe any significant change. On the other hand, a more detailed investigation of the presynaptic effects induced by Abeta42 by means of multiple probability fluctuation analysis and cumulative amplitude analysis showed an increase in both the size of the readily releasable pool responsible for synchronous release and the number of release sites. We further explored whether ryanodine receptors (RyRs) contributed to exacerbating these changes by stabilizing the interaction between RyRs and the accessory protein calstabin. We observed that the RyR–calstabin interaction stabilizer S107 restored the synaptic parameters to values comparable to those measured in control conditions. In conclusion, our results clarify the mechanisms of potentiation of GABAergic synapses induced by Abeta42. We further suggest that RyRs are involved in the control of synaptic activity during the early stage of AD onset and that their stabilization could represent a new therapeutical approach for AD treatment. Key points: Accumulation of the peptide amyloid beta 42 (Abeta42) is a key characteristic of Alzheimer's disease (AD) and causes synaptic dysfunctions. To date, the effects of Abeta42 accumulation on GABAergic synapses are poorly understood. The findings reported here suggest that, similarly to what is observed on glutamatergic synapses, Abeta42 modifies GABAergic synapses by targeting ryanodine receptors and causing calcium dysregulation. The GABAergic impairments can be restored by the ryanodine receptor–calstabin interaction stabilizer S107. Based on this research, RyRs stabilization may represent a novel pharmaceutical strategy for preventing or delaying AD. Abstract : Abstract figure legend Left: pre‐ and postsynaptic neurons are represented under physiological conditions. At rest, endoplasmic reticulum membrane contains ryanodine receptors (RyRs) in the closed state and the ratio between the sizes of the total readily releasable pool (RRPtot ) responsible for synchronous (RRPsyn ) and asynchronous (RRPasyn ) release is shifted towards RRPasyn . Middle: Abeta42 causes calcium dysregulation by targeting RyRs, which acquires a leaky conformation. Abeta42 potentiates the synchronous release and increases the ratio between the sizes of RRPsyn and RRPasyn, leaving unaltered the size of RRPtot . The number of release sites and the number of GABAergic receptors at the postsynaptic membrane are both increased by Abeta42. Right: S107, a RyCal compound, counteracts the effects induced by Abeta42 on GABAergic synapses by stabilizing RyRs in a close conformational configuration, recovering the size of RRPasyn and decreasing the number of release sites.